Net Deforestation and Clean Water Capacity as Determinants of the Environmental Quality Index in Indonesia: An Empirical Study 2018-2022 - Rosa Ambar Sari; Nur Hidayah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the effect of net deforestation, clean water capacity, domestic investment, and population density on the Environmental Quality Index (EQI) in Indonesia for the period 2018–2022. This study uses a quantitative method with panel data regression analysis in 25 provinces. The results show that net deforestation has a negative and significant effect on the Environmental Quality Index, while clean water capacity has a positive and significant effect. Meanwhile, domestic investment and population density do not have a significant effect on the EQI. These findings indicate that increased deforestation can reduce environmental quality, while increased clean water capacity can improve the environmental quality index. The government is advised to strengthen its deforestation control policies and expand clean water infrastructure development in order to achieve sustainable development in Indonesia.